KONSENTRASI SENG KLORIDA (ZnCl2) TERHADAP KARAKTERISTIK ARANG AKTIF KULIT BATANG SAGU - Marbun, Ricky , (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2025)
v>This study utilizes sago bark waste which has high lignin and cellulose content to beused as raw material for making activated charcoal with zinc chloride (ZnCl2). The purposeof this study was to obtain the best concentration of zinc chloride (ZnCl2) based on thecharacteristics of the sago bark activated charcoal produced. The charcoal was activated bysoaking the charcoal in zinc chloride (ZnCl2) solution for 24 hours with a mass ratio ofactivator to charcoal mass (4:1) with variations in zinc chloride (ZnCl2) concentrations,namely KA1 (ZnCl2 15%), KA2 (ZnCl2 20%), KA3 (ZnCl2 25%), KA4 (ZnCl2 30%), and KA5(ZnCl2 35%). The results of this study indicate that the concentration of zinc chloride has asignificant effect on the characteristics activated carbon. Activated carbon with the bestcharacteristics was obtained in the KA4 treatment with an activated carbon yield of 84.06%,a water content of 7.52%, ash content of 5.51%, volatile matter content of 14.90%, boundcarbon content of 72.05%, and iodine adsorption capacity of 752.94 mg/g. These results arein accordance with SNI No. 06–3730–1995.Keyword: activated carbon, sago bark, zinc chloride